2009
DOI: 10.5558/tfc85184-2
|View full text |Cite
|
Sign up to set email alerts
|

Population trend status of Ontario’s forest birds

Abstract: Recent population trends of Ontario's forest birds were assessed by integrating results across 8 bird surveys to provide an estimate of trend status for all of Ontario, and for 2 forested regions of Ontario separately. Surveys with mid-and longterm trends were relied on most extensively in this assessment. Comparison of the first and second Breeding Bird Atlases was especially important for estimating trends in northern forests, but overall reliability of status assessments in the north was considered poor due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 4 publications
1
26
0
Order By: Relevance
“…In addition, roads in several regions may be too dangerous to sample via roadside sampling. Thus, it is apparent that trends for these strata will require reliance either on off-road point counts or BBS style surveys (e.g., via all-terrain vehicle) such as those conducted for bird atlases (Blancher et al 2009), dedicated regional monitoring programs (e.g., Machtans et al 2014), or reliance on trends from the Christmas Bird Count (Niven et al 2004) or migration monitoring in combination with methods to infer catchment areas (Hobson et al 2015). As such, it would be beneficial to build on other work (e.g., Sólymos et al 2013, Amundson et al 2014 to develop and validate a framework for trend estimation from combining on-road and off-road point counts.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, roads in several regions may be too dangerous to sample via roadside sampling. Thus, it is apparent that trends for these strata will require reliance either on off-road point counts or BBS style surveys (e.g., via all-terrain vehicle) such as those conducted for bird atlases (Blancher et al 2009), dedicated regional monitoring programs (e.g., Machtans et al 2014), or reliance on trends from the Christmas Bird Count (Niven et al 2004) or migration monitoring in combination with methods to infer catchment areas (Hobson et al 2015). As such, it would be beneficial to build on other work (e.g., Sólymos et al 2013, Amundson et al 2014 to develop and validate a framework for trend estimation from combining on-road and off-road point counts.…”
Section: Resultsmentioning
confidence: 99%
“…Carlson and Schmiegelow (2002). Given pragmatic considerations the program would also have to integrate results from disparate methods such as point counts, migration monitoring, and other relevant studies such as was done qualitatively by Blancher et al (2009). Only then will we be able to make sense of the contrasting sources of information that often raise more questions than they answer.…”
Section: Bbs Sampling Coverage Issuesmentioning
confidence: 99%
“…Several regional studies have documented trends that differ from BBS results (e.g., Linder andBuehler 2005, Howe andRoberts 2005), and each other (Blancher et al 2009). Trend maps on the United States Geological Survey BBS website (http://www.mbr-pwrc.…”
Section: Local Habitat Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Local surveys and revisits to historic study areas have previously been used to provide external validation of reported trends (Machtans et al 2014), test hypotheses for the causes of trends (Holmes and Sherry 2001), and examine whether continent-wide declines reported from Christmas Bird Count (Butcher et al 1990) data reflect broad-scale vs. local declines on the breeding grounds (Machtans et al 2007). More recently, results from multiple monitoring programs across Ontario were integrated to provide broader insight and certainty around changes in species status and thereby address limitations and biases associated with individual monitoring programs (Blancher et al 2009). Blancher et al (2009) included off-road point-count data from the Ontario Breeding Bird Atlas, which was the primary source of trend data for 90% of species in the boreal shield (Bird Conservation Region [BCR] 8), highlighting the potential utility of local studies employing repeat visits to historic survey locations.…”
Section: Introductionmentioning
confidence: 99%